Respuesta :

Answer:

PQ = [tex]PM\cos MPQ + MQ\cos MQP=2PM\cos MQP[/tex]

Step-by-step explanation:

given MQR = 60, PQR = 75

MQP = 75 -60= 15[tex]QR = ((18(1+\cos 30))^{2}-(2\cos 15)^{2})^{\frac{1}{2}}[/tex]

WE KNOW THAT MQR +QRM +QMR = 180

MPQ = MQP AS ANGLE OPPOSITE TO EQUAL SIDES ARE EQUAL

THEREFORE QMR = 90 - 60 = 30

therefore PQM = 75 - 60 = 15

PM = PQ because M is the mid point

therefore PR = PM + [tex]MQ\cos QMR[/tex]

                PR = [tex]18(1+\cos 30)[/tex]

[tex]QR = (PR^{2}-PQ^{2}))^{\frac{1}{2}}[/tex]

PQ = [tex]PM\cos MPQ + MQ\cos MQP=2PM\cos MQP[/tex]